Differences of rape myth acceptance between genders: a systematic review - Wong, Weng See (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Understanding the differences in rape myth acceptance between genders can help individuals to gain a better view about rape myth related intervention and reduce sexual assault cases. Based on a systematic review, this paper summarized the recent findings and discuss about the underlying reasons behind rape myth acceptance, from the perspective of cultural of gender. 10 studies were chosen and males showed higher rape myth acceptance than female. Traditional gender roles, stereotypical view of power between both genders and sexual objectification of female appeared to be the predictor of this difference. Nevertheless, the other predictors such as level of rejection to equality, education and knowledge about sexual related issues and occupation of an individual played a bigger role than gender in special occasions.